Uczelnia XXI wieku. Sieć społeczna studentów, absolwentów i kadry naukowodydaktycznej w innowacyjnym modelu kształcenia ideAGORA - Maj , Konrad (Studia Edukacyjne, 2017)
This article presents the contemporary challenges faced by universities. It focuses on the traditional and the modern approach to the University maintaining relations with their socio-economic environment. These relationships are described in the framework of the social network theory. The second part presented an innovative model of education ideAGORA, the concept of lifelong learning based of a lasting relationship between university and graduate. The results of evaluations carried out after the stage of testing the ideAGORA model demonstrated its high efficiency: it contributes to strengthening alumni’s ties with the University, the sincerity of their motivation to study and activity as well as the interest in additional training in the case of graduates and academic staff.